Risk Factors of Stunting among 1-2 Years Old Children in Semarang City - Aryu Candra; Niken Puruhita; JC Susanto (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTBackground: Prevalence of stunting in children under five years in Central Java is high, more than 33%. Semarang City has high prevalence of malnutrition therefore there is a need to identify risk factors of stunting in Semarang city.Method: This was a case control study, completed with qualitative study about risk factors of stunting. Samples were 58 cases and 58 controls. Data were analyzed by univariate analysis, bivariate analysis with chi square test, and multivariate analysis with multiple logistic regression. Qualitative study was done by using indepth interview, and presented in narration.Results: The multivariate analysis result showed that risk factors of stunting in children 1-2 years old were short stature father (<162 cm) (p=0.016; OR=2.7; CI=1.2-6), children had history of low birth weight (p=0.028; OR=11.2; CI=1.3-96.3), and children had history of underweight (p=0.006; OR=3.3; CI=1.4-7). Risk factors which were not proven to influence the incidence of stunting were maternal height, history of exclusively breastfed, complementary feeding history; sex, history of infection, and immunization history.Conclusions: Risk factors that influence the incidence of stunting in children 1-2 years olds are having father’s height <162 cm, and positive history of low birth weight, and of underweight.Keywords: Stunting, malnutrition, children, growth, risk factorsABSTRAKFaktor risiko dari stunting pada anak usia 1-2 tahun di kota SemarangLatar belakang: Stunting adalah perawakan pendek yang timbul akibat malnutrisi yang lama. Prevalensi stunting pada balita di Jawa Tengah tinggi, yaitu lebih dari 33%. Kota Semarang merupakan ibukota Jawa Tengah yang memiliki prevalensi malnutrisi cukup tinggi sehingga diperlukan studi untuk mengetahui faktor risiko stunting di Kota Semarang.Metode: Penelitian ini merupakan studi kasus kontrol, dilengkapi kajian kualitatif mengenai stunting pada status ekonomi kurang dan status ekonomi cukup. Jumlah sampel 58 kasus dan 58 kontrol. Analisis data dilakukan secara univariat, bivariat dengan chi square test, multivariat dengan metode regresi logistik ganda. Kajian kualitatif denganmetode indepth interview dan disajikan dalam bentuk narasi.Hasil: Hasil analisis multivariat menunjukkan faktor risiko yang berpengaruh terhadap kejadian stunting pada anak 1-2 tahun di kota Semarang adalah tinggi badan ayah <162 cm (p=0,016; OR=2,7; CI:1,2-6), anak yang mempunyai riwayat BBLR (p=0,028; OR=11,2; CI=1,3-96,3), dan anak mempunyai riwayat underweight (p=0,006; OR=3,3; CI=1,4-7). Faktor risiko yang tidak terbukti mempengaruhi kejadian stunting adalah jenis kelamin, tinggi badan ibu, riwayat ASI eksklusif, riwayat infeksi, riwayat imunisasi, dan riwayat makanan pendamping ASI.Simpulan: Faktor risiko yang mempengaruhi kejadian stunting pada anak 1-2 tahun adalah yang mempunyai ayah dengan tinggi badan <162 cm dan mempunyai riwayat BBLR, serta berat badan kurang.